In Vitro Evaluation of Flow and Working Time of AH Plus Alone and in Combination with Amoxicillin and Triple Antibiotic Paste - Mojdeh Mashhadi Esmaeili; Maryam Zare Jahromi; Maziyar Ebrahimi Dastjerdi (Islamic Dental Association of Iran, 2015)
Background and Aim: Some researchers have attempted to enhance the antibacterial properties of sealers by addition of antibiotics while this may affect their physical properties. The purpose of this in vitro study was to compare the working time and flow of AH Plus sealer alone and in combination with amoxicillin and triple antibiotic paste (TAP). Materials and Methods: This in vitro study assessed the flow and working time of AH Plus alone (control group) and in combination with amoxicillin and TAP in 1%,5%, 10% and 25% concentrations according to ANSI/ADA specification NO. 57. The data were analyzed by ANOVA and Tukey's test. Results: Statistically significant differences were noted in the flow and working time of the control group with those of different concentrations of TAP in combination with sealer (P<0.0001). The working time decreased by an increase in the concentration of TAP. The AH Plus/1% TAP and AH Plus/5% TAP showed higher flow than the control group. The AH plus/1%amoxicillin, AH Plus/5% amoxicillin and AH Plus/10% TAP had a flow similar to that of the control group. Other groups showed lower flow than the control group. Conclusion: All the alterations in the physical properties of AH Plus sealer in combination with amoxicillin and TAP were within the ANSI/ADA specification NO. 57 standard range.